Climate Resilience in Nigerian Construction: A Systematic Review of Strategies and Outcomes - Unegbu, Hyginus C. O.; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Universitas Katolik Parahyangan, 2024)
Climate resilience in the construction sector is critical for ensuring the durability and sustainability of infrastructure amidst the increasing impacts of climate change. This study systematically reviews climate resilience strategies in the Nigerian construction sector, evaluating their effectiveness and outcomes. A comprehensive literature search yielded 50 peer-reviewed journal articles, conference papers, and official reports, focusing on design innovations, material selection, policy frameworks, and case studies across Nigeria's diverse climatic zones. Key findings indicate that strategies such as flood barriers, green roofs, and sustainable materials are effective in mitigating climate risks, although challenges such as financial constraints, regulatory gaps, and lack of awareness persist. The study highlights the importance of community involvement, government support, and technological innovation in successfully implementing resilience measures. Comparative analysis with global best practices underscores the need for integrated approaches tailored to Nigeria's unique context. The study concludes with recommendations for future research, emphasizing the need for longitudinal studies, cross-regional comparisons, and the integration of traditional knowledge. Policy implications include the development of comprehensive regulatory frameworks and public-private partnerships to enhance the sector's adaptive capacity. This research provides valuable insights and practical recommendations for enhancing climate resilience in Nigeria's construction industry, contributing to broader goals of sustainable development and climate adaptation.